Role of flux on synthesis of poly single crystals of Ce3+ doped yttrium aluminum garnet page 239–242 by Q.L. Liu et al. Issue 3 (March 2016) - Song, Zhen; Zu, Rui; Liu, Xiaolang; He, Lizhu; Liu, Q.L.
Abstract : Yttrium aluminum garnet powders of good morphology are composed of tiny single crystals of regular faces. It is found that those tiny crystals grow from large clusters. The pomegranate‐like growth mechanism is driven by flux, which provides a semi‐liquid environment around the crystals.